2017
DOI: 10.3389/fendo.2017.00231
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Cortical and Hippocampal Expression of Genes Important for Brain Glucose Metabolism Following Controlled Cortical Impact Injury in Mice

Abstract: Traumatic brain injury (TBI) causes transient increases and subsequent decreases in brain glucose utilization. The underlying molecular pathways are orchestrated processes and poorly understood. In the current study, we determined temporal changes in cortical and hippocampal expression of genes important for brain glucose/lactate metabolism and the effect of a known neuroprotective drug telmisartan on the expression of these genes after experimental TBI. Adult male C57BL/6J mice (n = 6/group) underwent sham or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 72 publications
1
24
1
Order By: Relevance
“…In comparison with our previous results in the acute phase of TBI induced by controlled cortical impact (35), the expression of genes encoding glucose or lactose transporters was not affected by mTBI in any of the brain regions measured. Further, expression of genes encoding HK1 and PFK, two of four rate limiting enzymes in glucose metabolism, was not significantly altered in any of the assessed brain regions.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In comparison with our previous results in the acute phase of TBI induced by controlled cortical impact (35), the expression of genes encoding glucose or lactose transporters was not affected by mTBI in any of the brain regions measured. Further, expression of genes encoding HK1 and PFK, two of four rate limiting enzymes in glucose metabolism, was not significantly altered in any of the assessed brain regions.…”
Section: Discussioncontrasting
confidence: 77%
“…We previously reported that hippocampal and cortical expression of genes important for brain glucose utilization were all altered by TBI from 6 h to 28 days post brain injury ( 35 ). Those observed temporal alterations in gene expression corresponded closely to temporal alterations in brain glucose utilization reported in TBI patients and experimental animals during the acute and subacute phases of TBI ( 12 17 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, patients with aberrant glucose utilization and network activity during the first week post-TBI have worsened outcomes 6 months later (57). Preclinical work from multiple animal models of TBI shows early increases in glucose utilization (33,(58)(59)(60)(61) which are activity-dependent (34). Consistent with focal hyper-glycolysis and network dysfunction, our previous studies show heightened glutamate signaling in the peri-injury cortex and parvalbumin-interneuron loss also regionally confined to this area.…”
Section: Discussionsupporting
confidence: 52%
“…These changes provide insight into which processes are up- or down-regulated following injury. Examination of the transcriptome after CCI in mice shows increased expression of glycolytic enzymes at 6 h after injury, with later decreases in glycolytic enzyme expression at later time points ( Zhou et al, 2017 ). Similarly, severe FPI in rats resulted in increased expression and enzymatic activity of proteins involved in glycolysis at early time points after injury ( Amorini et al, 2016 ).…”
Section: Glucose Metabolism Is Dysregulated Following Traumatic Brainmentioning
confidence: 99%